Use of thermoplastic starch in poly(lactic acid)/poly(butylene adipate-co-terephthalate) based nanocomposites for bio-based food packaging - Manepalli, Pavan Harshit (Kansas State University, 2019)
Poly(lactic acid) (PLA) is the most common bio-based & compostable polymer available commercially that is cost competitive and combines a range of desirable properties like melt processability, high strength and modulus. The films made from this aliphatic polyester tend to be brittle which can be overcome by blending PLA with another bio-based polymer with high flexibility poly(butylene adipate-co-terephthalate) (PBAT), but the resultant blend is only biodegradable in composting conditions. The primary focus of this study was incorporation of thermoplastic starch (TPS) in PLA/PBAT blends to increase the rate of biodegradability and decrease the cost. In the first part of this study, as a preliminary step only PLA/PBAT blends were investigated along with nanofiller nanocrystalline cellulose (NCC) as a nanofiller for enhancing mechanical and barrier properties. Melt extrusion was used for preparation of nanocomposites and 200 microns thick films were formed by melt pressing. PBAT enhanced elongation but NCC did not have any positive impact on the mechanical and barrier properties of the nanocomposites as NCC was aggregated in the polymer matrix due to the difference in polarity based on the hydrophilic nature of the nanofiller and hydrophobic nature of the polymer matrix. In the second part of study, up to 40%TPS was blended along with the PLA/PBAT/NCC nanocomposites. Joncryl (0.5%) was used as a compatibilizer. TPS addition decreased the mechanical and barrier properties (Tensile strength (TS) = 15- 30 MPa, Elongation at break (EB) = 6-12%, Water vapor permeability (WVP) = 1.6-8.3 g.mm/kPa.h.m²), although addition of NCC helped in increasing the TS and decreasing the WVP. Dispersion of NCC improved with the addition of hydrophilic TPS. Analytical techniques including transmission electron microscopy, fourier-transform infrared spectroscopy, differential scanning calorimetry were used to study the polymer-polymer and polymer-nanofiller interactions. Optimization study of PLA/PBAT/TPS/NCC nanocomposites was done using mixture response surface methods. Quadratic models with good predicted R² (between 84.3% and 97.59%) were developed for all the responses. Optimization study was done that could yield films with optimum properties comparable to commercial plastics and maximizing the level of TPS. Films with optimum properties (TS = 29.5 MPa, EB = 12%, WVP = 1.99 g.mm/kPa.h.m²) were predicted at levels of 64.3% PLA, 14.5% PBAT, 18% TPS and 2.6% NCC along with 0.5% Joncryl. The improved mechanical and barrier performance suggested that PLA/PBAT/TPS/NCC nanocomposites have potential use in food packaging applications. In the final phase of study, mathematical modeling was used to understand the influence of nanofiller (NCC) on the mechanical and barrier properties of the nanocomposites. The modified Halpin-Tsai equation was used to model the elastic modulus of the nanocomposites, while the modified Nielsen equation was used to model the WVP as a function of nanofiller content, geometry, strength and interactions with polymer matrix. The experimental results in both cases were close to the theoretical predictions by the models. The models predicted an increase in mechanical and barrier properties with increase in aspect ratio and surface interactions of nanofiller with polymer matrix.
Keywords: Food Packaging; Nanocomposites